The Influence of Learning Discipline and Learning Facilities on Learning Achievement with Parental Support as a Moderating Variable for Vocational School Students Majoring in Accounting in East Jakarta - Nadya indah Wulandari; Ati Sumiati; Dwi Kismayanti Respati (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
The aim of this research is to find out whether learning discipline influences learning achievement, learning facilities influence learning achievement, parental support moderates the influence of learning discipline on learning achievement, and parental support moderates the influence of learning facilities on learning achievement among vocational school students majoring in accounting in Jakarta East. The research was carried out in SMKN 10, SMKN 40, and SMKN 48. This research uses quantitative research with survey methods.The population came from State Vocational School students majoring in accounting in East Jakarta. The sampling technique used in this research was simple random sampling. The total sample was 168 respondents. Data collection technique used was a questionnaire processed with SPSS and documentation. The results show that learning discipline has an effect on learning achievement, learning facilities have no effect on learning achievement, learning discipline moderated by parental support has an influence on learning achievement, learning facilities moderated by parental support has no effect on learning achievement. Recommendations for further research are:can explore other factors that influence learning achievement, expand the area of ​​data collectionso that new things can be discovered that can influence performance Study.